The Efficacy of Amruta Guggulu (Internal) and Madhuyashtyadi Taila (External) in the Management of Vatarakta w.s.r. to Gouty Arthritis (AYUSHDHARA, 2024)
Ayurveda is the only medical science which has focused more on prevention of diseases and maintenance of health. The system advocates for a balance between lifestyle, diet, upright attitude. In the modern context of life, people and their dietary habits, lifestyle, social structure and environment have undergone a remarkable change leading to many avoidable diseases. Vatarakta is one among those diseases. The name Vatarakta indicates the unique pathology of morbid Vata dosha and Rakta dhatu. Based on aetiolgy, pathogenesis, signs and symptoms Vatarakta can be compared with Gouty Arthritis of contemporary medicine. It is a painful metabolic disorder caused due to hyperuricemia, which in turn is caused by genetic factors, dietary factors which are rich in purine, alcohol consumption, drugs, smoking and lack of physical activity. In moderns medicine Gouty Arthritis is treated by NSAIDS, steroids, uricosuric agents, allopurinol, febuxostat etc. But in due course all these drugs can lead to adverse effects when used for long duration. This causes additional trouble to the patients. Keeping this in view, there is a need for simple, safe and effective treatment. Hence this study has been initiated to evaluate the clinical efficacy of Amruta guggulu (internal) and Madhuyashtyadi taila (external) in the management of Vatarakta w.s.r to Gouty Arthritis.